Hypercalcaemia in infancy; a presenting feature of spinal muscular atrophy. Issue 4 (19th March 2004) - Khawaja, K; Houlsby, W T; Watson, S; Bushby, K; Cheetham, T
Abstract : A 10 month old girl presented with a history of constipation from early life. She was found to be hypercalcaemic with hypercalciuria and nephrocalcinosis. Her mild motor delay and hypotonia were thought to be linked to chronic hypercalcaemia, but when these features failed to improve despite normocalcaemia on a low calcium diet the possibility of neuromuscular disease was explored in more detail. She was subsequently found to have spinal muscular atrophy type 2. We suspect that the hypercalcaemia with hypercalciuria observed in this case reflects altered bone turnover secondary to reduced muscular activity.